Analisis Kinerja Dan Minimasi Waste Proses Produksi Gula Semut Menggunakan Metode Lean Six Sigma - Setyo Ananto Wibowo; Cyrilla Indri Parwati; Mega Inayati Rif’ah (Universitas Sarjanawiyata Tamansiswa, 2021)
CV. XÃ‚Â is a company that produces palm sugar. The company is located at Yogyakarta. The main problem in the production process at CV. X is that there is still waste in the flow of production. The waste defect that occurs still exceeds the defect tolerance limit targeted by the company, which is 2%, while the waste defect found is 5%. In addition, waste waiting was found in the form of an accumulation of 500 kg of semi-finished goods in the production area due to a bottleneck at the packaging workstation. This research was conducted to determine the ability of the production process based on defective products and the time of the production process using the Lean Six Sigma approach, which was then carried out using Kaizen. Based on data processing, the DPMO value is 7571.83 with the company's sigma value is 3.92 sigma. Percentage of activity based on Process Activity Mapping (PAM) before improvement, the value added activity was 83.71%, non-value added activity was 11.84%, and necessary but non-value added activity was 4.45%. Meanwhile, after the improvement, the value added activity was 86.85%, non-value added activity was 7.78%, and necessary but non-value added activity was 5.37%. The main causes of waste in the production process of palm sugar are human factors, machines, raw materials, methods, and the environment. Based on the kaizen implementation tools, the proposed improvement for the company is to conduct inspection and supervision in all fields and determine the ideal number of packaging workers in order to minimize waste that occurs.